Comparative effects of selenium nanoparticles and sodium selenite on selenium bioaccumulation in quail tissues and its transfer to progeny - Sania Satti; Shabana Naz; Rifat Ullah Khan; Abdulwahed Fahad Alrefaei; Mikhlid Almutairi; Naseer Khan Momand; Demilade Israel Ibiwoye (Journal of Applied Animal Research, 2025)
Selenium nanoparticles (Se-NPs) and sodium selenite (SS) play key roles in avian health, but differ in absorption and toxicity. This study compared their effects on growth, productivity, and selenium bioaccumulation in adult quails and hatchlings (up to 2 weeks post-hatch). A total of 480 quails (8 weeks old) were divided into five groups: a control (basal diet), two groups with Se-NPs (0.2 and 0.4 mg/kg), and two with SS (0.2 and 0.4 mg/kg). Each group had 96 birds, arranged in six replicates with a 1:3 male-to-female ratio. Quails receiving 0.4 mg/kg Se-NPs showed the highest body weight gain, lowest feed conversion ratio, and best survival. The 0.2 mg/kg Se-NPs group had the highest egg weights, while the 0.4 mg/kg Se-NPs group produced the greatest egg mass. Selenium accumulation was highest in the liver of birds supplemented with 0.4 mg/kg Se-NPs. Similar patterns were observed in hatchlings, with elevated selenium levels persisting for two weeks post-hatch. The findings suggest Se-NPs are more effective than SS in enhancing growth, productivity, and selenium retention in quails.